Somme the heroism and horror of war - Gilbert, Martin 1936- (John Murray, 2007)
Fought between July and November of 1916, the Battle of the Somme was one of the bloodiest conflicts of all time. In this book, Martin Gilbert graphically recreates the tragedy, interweaving individual stories, wartime documents, letters and poetry in a moving and succinct narrative.